A Conceptual Approach for Innovative Home Care Solution - Lucia RUSU (Journal of Applied Computer Science & Mathematics, 2014)
The goal of this paper is to develop a collaborative model of a network infrastructure for innovative home care solutions. Based on classification scheme for Living Assistance Domain (LAD) we develop a prototype for elders and people with disabilities which includes Emergency Treatment Services, Autonomy Enhancement Services and Comfort Services for indoor assistance. The model was developed based on end-users and formal carers requirements and includes advanced IT services: monitoring and navigational support which are needed to support the mobility of elders and disabled persons in their home during daily activities. Our solution provides simple and interactive functions for login end-users and communicates with caregivers or other members of social community.